Economic Growth and the Environmental Degradation: the Review of the Scientific Research - Lapinskienė, Giedrė; Peleckis, Kęstutis; Peleckienė, Valentina (IJRDO - Journal of Applied Management Science, 2017)
Since the 1970s, when the Club of Rome put forth the theory of “The Limits to Growth“, the environmental quality has been considered a new prerequisite for economic growth. The idea has passed from academic and environmental activists to political handling. In the academic world, the centre of this discussion was so called the environmental Kuznets curve, representing the relationship between various indicators of environmental degradation and economic growth. The environmental Kuznets curve indicates that, at the early stages of economic growth, pollution increases with the growing use of resources, but when a certain level of income per capita is reached, the trend reverses so that, at a higher development stage, further economic growth leads to the improvement of the environment. The aim of this paper is to describe the evolution of the environmental Kuznets curve, starting from its roots till nowadays, to summarise and systemise the results of empirical studies of the relationship between the air quality indicators (due to global climate change) and economic growth. In the article the most influential theories of the environmental economics are described in order to highlight the strong environmental approach. The article may be useful for scientists and policy makers, analysing the trends of the economic development of the countries, and dealing with the problems of the relationship between the environmental indicators and economic growth.